Electric current-restrained crack propagation in brittle GaN ceramics - Zhao, M.H.; Umair, M.; Lu, Chunsheng; Qin, G.S. (SPRINGER, 2021)
© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature. The reliability of a ceramic structure or device is closely related to its faults, such as structural defects and cracks. Here, we show that cracking in piezoelectric semi-conductive ceramics (PSCs) can be restrained with the application of an electric current. Due to the crack-generated flexoelectricity, piezoelectric polarization charges that generate and gather on the front of a crack result in a strong thermoelectric effect. The phase transition and plastic deformation happened near a crack tip can hinder the propagation of the crack and even lead to its partial closure. These new findings are instructive to study the crack control and the design of PSC devices with damage tolerance.